The search for alignment of board gender diversity, the adoption of environmental management systems, and the association with firm performance in Asian firms. (5th May 2020) - Rehman, Saif; Orij, René; Khan, Hashim
Abstract: This study examines how board gender diversity can address the challenges to adopt environment management systems (EMS) to improve firm performance. Firstly, drawing on gender socialization and diversity theories, higher board gender diversity motivates firms to adopt EMS. Empirical evidence shows that firms with gender diverse boards are greener. Secondly, the study investigates the maxim that green pays to be green. The empirical findings highlight a positive and statistically significant but economically modest link between EMS and firm financial performance. However, the inclusion of board gender diversity as moderator significantly improves the relationship between EMS and firm performance. In addition, CEO gender is linked to better performance only in firms with low female board diversity. The findings strongly recommend higher board gender diversity as a mechanism to address the challenges of EMS and firm performance simultaneously. The findings are robust to controlling for propensity score matching technique and are different in different approaches.